2005
DOI: 10.1007/s10681-005-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation for winter hardiness generated by androgenesis from Festuca pratensis × Lolium multiflorum amphidiploid cultivars with different winter susceptibility

Abstract: Androgenic populations produced from three Festuca pratensis × Lolium multiflorum amphidiploid (2n = 4x = 28) cultivars show wide within population variation for winter hardiness. Populations comprising a total of 423 androgenic plants derived from 23 donor plants from 3 Polish F. pratensis × L. multiflorum cultivars Felopa, Sulino, and Rakopan were studied over 3 years (1999)(2000)(2001)(2002) in a field experiment at Lopuszna, Poland (20 • 08 E, 49 • 28 N, altitude 568 m). The results indicate that despite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…F. pratensis is a known good source of genes for winter-hardiness (Humphreys et al 1997). However, it is remarkable in the androgenic lines that despite the reduced F. pratensis gene complement, and their combination with genes from the freezingsensitive L. multiflorum genome, that the resilience to extreme low temperatures in the field is retained and in many cases increased above that of the Festuca parent (Rapacz et al , 2005. The field studies revealed a strong negative correlation over 2 years (-0.71 and -0.67) between maximum quantum yield of PSII (F v /F m ) before winter and subsequent winter survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…F. pratensis is a known good source of genes for winter-hardiness (Humphreys et al 1997). However, it is remarkable in the androgenic lines that despite the reduced F. pratensis gene complement, and their combination with genes from the freezingsensitive L. multiflorum genome, that the resilience to extreme low temperatures in the field is retained and in many cases increased above that of the Festuca parent (Rapacz et al , 2005. The field studies revealed a strong negative correlation over 2 years (-0.71 and -0.67) between maximum quantum yield of PSII (F v /F m ) before winter and subsequent winter survival.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated conclusively that regenerant genotypes derived following androgenesis from Lolium · Festuca hybrids include gene combinations difficult to recover through conventional backcross breeding programmes (Humphreys et al 1998. Furthermore, many examples were demonstrated where androgenesis enhanced gene expression for complex traits such as drought resistance Zare et al 2002) or freezing-tolerance (Humphreys et al 2000;Zare et al 1999;Rapacz et al 2005), in excess of that found in the parent genotypes. In this way androgenesis was shown to be a technology capable of exploiting the genetic potential of a genotype, that otherwise in its unreduced disomic state, was under-expressed due to combinations of control by recessive alleles, or possible pleiotropic or epistatic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000). Recent research has demonstrated that genotypes with high winter hardiness or snow mould resistance were recovered at equal frequencies in androgenic populations derived from both resistant and susceptible parent genotypes and cultivars (Rapacz et al . 2005).…”
Section: Intergeneric Hybridization Between Lolium and Festucamentioning
confidence: 99%
“…Different cultivars of Festulolium braunii -perennial grass which non-obligatorily requires vernalization -were chosen as the subject of this study. It should be noted that F. braunii is a hybrid obtained from special intergeneric Festuca pratensis 9 Lolium multiflorum crosses, having achieved both the high level of winter-hardiness (from F. pratensis) and the good feeding value (from L. multiflorum) (Rapacz et al 2005, Kopeck y et al 2006, Opitz et al 2006.…”
Section: Introductionmentioning
confidence: 99%